A Comparative Analysis of the American and Chinese Pharmaceutical Industries - McConnell, Liam H. (My University, 2022)
Following the growth of the Chinese pharmaceutical consumer market and innovative capability, comparisons between the American and the Chinese pharmaceutical industries have become commonplace due to two very divergent governmental, competitive, financial, and knowledge environments, as scholars and businesspeople alike attempt to predict shifts in power dynamics. Previous pharmaceutical industry research has focused on a single country, broad industry analysis (Ni, et al., 2017), or has conducted specific cross-border comparisons which fail to consider the respective macro-environments (Jiang & Luan, 2018; Zhao M. , 2021). This literary review examines four environments relevant to pharmaceutical innovation to achieve a broad and comparable understanding of the two industries, ultimately finding that the American industry is a well-established player focused on highly innovative activities, while the Chinese industry is a relative newcomer that is quickly developing innovative capabilities relevant to global competition dynamics.